Pengaruh Penggunaan Media Video Presentasi Terhadap Pemahaman Siswa Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMAN 3 Bengkalis - Khairunnisa, Iqlima; Promadi, Promadi; Yeli, Salmaini (CV. Rayyan Dwi Bharata, 2025)
This research aims to examine the effect of using video presentation media on improving students’ understanding in the subject of Islamic Religious Education and Character at State Senior High School 3 Bengkalis. The background of this investigation is based on the low level of student comprehension due to the use of conventional teaching methods that lack variety. A quantitative approach was employed using a true experimental design in the form of a pretest-posttest control group design. The sample consisted of two classes: class X.1 as the experimental group, which used video presentation media, and class X.2 as the control group, which applied conventional methods. The research instruments included an objective test comprising 10 multiple-choice questions and an observation sheet. The data were analyzed using tests of validity, reliability, normality, and homogeneity, as well as the Wilcoxon test with the assistance of SPSS version 25. The result of the Wilcoxon test showed a significance value of 0.000. Based on the criteria (Sig. 0.05), this means the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted, indicating a statistically significant difference in students’ understanding between those taught using video presentation media and those taught using conventional methods. In conclusion, the findings demonstrate that video presentation media has a positive effect on enhancing students’ understanding of Islamic Religious Education and Character.